2018
DOI: 10.4103/0366-6999.243551
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particulate Matter-Induced Exacerbation of Allergic Asthma via Activation of T-cell Immunoglobulin and Mucin Domain 1

Abstract: Background:Fine particulate matter (PM2.5) exacerbates airway inflammation and hyperreactivity in patients with asthma, but the mechanism remains unclear. The aim of this study was to observe the effects of prolonged exposure to high concentrations of PM2.5 on the pathology and airway hyperresponsiveness (AHR) of BALB/c mice undergoing sensitization and challenge with ovalbumin (OVA) and to observe the effects of apoptosis and T-cell immunoglobulin and mucin domain 1 (TIM-1) in this process.Methods:Forty femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
(42 reference statements)
0
15
0
1
Order By: Relevance
“…Previous studies have confirmed that PM2.5 exposure could cause acute airway inflammation 15,16 . In the present study, we explore the effect of PM2.5 on pulmonary inflammation in vivo.…”
Section: Resultsmentioning
confidence: 82%
“…Previous studies have confirmed that PM2.5 exposure could cause acute airway inflammation 15,16 . In the present study, we explore the effect of PM2.5 on pulmonary inflammation in vivo.…”
Section: Resultsmentioning
confidence: 82%
“…Fine particulate matter (PM 2.5 , particle size < 2.5 μ m) generally has greater toxicity than other particles due to its smaller diameter and larger surface-to-mass ratio, thus allowing it to enter into the lower respiratory tract and even penetrate into the alveolar space and ultimately into the blood circulation [1]. PM 2.5 exposure can induce lung inflammation and airway hyperresponsiveness (AHR) and can even increase the risk of developing asthma [2, 3]. The underlying mechanisms of PM 2.5 toxicity may be partly explained by its ability to cause oxidative stress and mitochondrial damage [4], a process that involves the activation of pattern recognition receptors (PRRs), such as Toll-like receptors (TLRs) and nucleotide binding domain leucine-rich repeat-containing receptors (NLRs) [5].…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 had been obtained by filtering ambient air followed by up-concentration, however, the exact chemical composition was not elucidated. One of the studies attributed the elevated AHR to an increase in apoptosis and TIM-1 activation, which was also witnessed in the OVA/PM 2.5 group (156). Another study has shown that prolonged exposure to high concentrations of PM 2.5 leads to an increase in AHR, which was linked to necroptosis-induced neutrophils as well as IL-17 production (158).…”
Section: Aggravation Of Allergic Asthma By Inhaled Aerosolsmentioning
confidence: 94%